Modeling of SOL helical current filaments induced by biased electrode on J-TEXT. (11th October 2021) - Li, Shuhao; Wang, Nengchao; Ding, Yonghua; Song, Zebao; Liang, Yunfeng; Yang, Qinghu; Mao, Feiyue; Huang, Zhuo; Shen, Chengshuo; Bala, Abba Alhaji; Chen, Zhipeng; Chen, Zhongyong; et al.
Abstract: It has been demonstrated in J-TEXT experiments that a biased electrode or electrode biasing (EB) in the scrape-off layer (SOL) can drive SOL helical current filaments (HCFs). The bright helical radiation belts of carbon impurities in the SOL indicate that SOL current flows along the magnetic field lines. Based on the experimental phenomenon, three SOL current models (model A, B, C) have been set-up in order to understand the spatial structure of SOL current and the perturbed magnetic field it generates. Model A is a simplified calculation of HCFs in the cylindrical geometry, and takes into account the presence of cross-field current by a linear decay of current along magnetic field lines. Model B take into account the actual toroidal geometry and the complex path of HCFs connected from the electrode to the limiters. By including the radial dependence of the resistivity into model B, model C is developed and describes the SOL current more perfectly than the other two models. Furthermore, the model C shows that SOL helical current can produces stronger boundary resonant magnetic perturbations (RMPs) at the last closed flux surface (LCFS) due to the consistent helixity of SOL current filaments and the boundary rational surface, which may be a new way to generate RMPs to control the edge-localized modes (ELMs). The equivalent inductance and resistance of HCFs at different edge safety factor q a are measured by applying a square wave voltage. The results show that the inductance and resistance of the HCFs are related to q a and the radial position of the biased electrode r EB, in a qualitatively consistent manner as that predicted by model C.